2013
DOI: 10.1039/c3cc42037j
|View full text |Cite
|
Sign up to set email alerts
|

A general strategy for obtaining biodegradable polymer shelled microbubbles as theranostic devices

Abstract: Fabrication of multifunctional ultrasound contrast agents (UCAs) has been recently addressed by several research groups. A versatile strategy for the synthesis of UCA precursors in the form of biodegradable vesicles with a biocompatible crosslinked polymer shell is described. Upon ultrasound irradiation, acoustic droplet vaporization transforms such particles into microbubbles behaving as UCAs. This proof of concept entails the features of a potential theranostic microdevice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
(6 reference statements)
2
24
0
Order By: Relevance
“…Capece et al [32] reported a novel strategy for generation of biocompatible polymer-shelled MBs from biodegradable vesicles that underwent ultrasound irradiation via ADV. They produced PFC core droplets covered with surfactant layer, which was attached to a hydrophilic polymer grafted with a vinyl moiety.…”
Section: Capsule Design and Productionmentioning
confidence: 99%
“…Capece et al [32] reported a novel strategy for generation of biocompatible polymer-shelled MBs from biodegradable vesicles that underwent ultrasound irradiation via ADV. They produced PFC core droplets covered with surfactant layer, which was attached to a hydrophilic polymer grafted with a vinyl moiety.…”
Section: Capsule Design and Productionmentioning
confidence: 99%
“…[1][2][3] To date, most of the organic, inorganic, and compound theranostic agents developed contain polymer particles, magnetic nanoparticles, quantum dots, and novel metal substrates. 11,12 By coupling MBs and Lipos as a complex, this concept material has been shown to achieve simultaneous ultrasound (US) imaging of cells as well as highly efficient targeted delivery of therapeutic loads. [4][5][6][7] The potential toxicity of the constituent materials (especially the inorganic nanoparticles) raises significant safety concerns and toxicological evidence, all of which need to be carefully addressed prior to their clinical applications.…”
mentioning
confidence: 99%
“…MBs stabilized by solid shells, such as core–shell polymeric microcapsules, have also been explored as intravascular gas carriers. A solid polymeric shell offers several natural advantages over their lipid counterparts . The presence of solid shells permanently stabilizes the gas core and effectively eliminates coalescence and Ostwald ripening.…”
Section: Oxygen‐filled Hard‐shelled Polymeric Microbubblesmentioning
confidence: 99%